Σκόλοψ τῇ σαρκί in 2 Cor 12,7 - Callan, Terrance (Biblica, 2025)
This essay first surveys the history of interpretation of 2 Cor 12,7; it then discusses the uses of σκόλοψ in Greek literature; and finally it argues on the basis of this usage and exegesis of 2 Cor 12,7 that σκόλοψ in this passage should be understood as meaning 'stake', a means of execution like the σταυρός that was the means of executing Jesus.